The Quebec connection : a poetics of solidarity in global francophone literatures - Tolliver, Julie-Françoise, 1980- (New World studies., 2020)
"The first full-length study of the literary solidarity reciprocities connecting Quebec to the francophone anticolonial movement, this book examines the poetics of solidarity to offer precise and eloquent evidence of both the possibilities and the limits of shared language as a site for transnational political agency"--